Nitrogen and Chemical Control Management Improve Yield and Quality in High-Density Planting of Maize by Promoting Root-Bleeding Sap and Nutrient Absorption - Liu, Xiaoming; Zhang, Liguo; Yu, Yang; Qian, Chunrong; Li, Congfeng; Wei, Shi; Li, Caifeng; Gu, Wanrong (Frontiers in Plant Science, 2022)
High-density planting aggravates competition among plants and has a negative impact on plant growth and productivity. Nitrogen application and chemical control can improve plant growth and increase grain yield in high-density planting. Our experiment explored the effects of nitrogen fertilizer and plant growth regulators on maize root-bleeding sap, phosphorus (P) and potassium (K) accumulation and translocation, and grain yield and quality in high-density planting. We established a field study during the 2017 and 2018 growing seasons, with three nitrogen levels of N100 (100 kg ha−1), N200 (200 kg ha−1), and N300 (300 kg ha−1) at high-density planting (90,000 plants ha−1), and applied Yuhuangjin (a plant growth regulator mixture of 3% DTA-6 and 27% ethephon) at the 7th leaf. Our results showed that N200 application combined with chemical control could regulate amino acid and mineral nutrient concentration delivery rates in root-bleeding sap and improve its sap rate. Also, the treated plant exhibited higher P and K uptake and translocation ability. Furthermore, chemical control and N200 treatment maintained a high level of ribulose-1,5-bisphosphate carboxylase (RuBPCase), phosphoenolpyruvate carboxylase (PEPCase), nitrate reductase (NR), and glutamine synthetase (GS) enzymatic activities in leaves. In addition, plant growth regulator and nitrogen application improved the enzymatic activities of GS, glutamate dehydrogenase (GDH), and glutamic pyruvic transaminase (GPT) and the contents of crude protein, lysine, sucrose, and soluble sugar in grain and ultimately increased maize yield. This study suggests that N200 application in combination with chemical control promotes root vitality and nutrient accumulation and could improve grain yield and quality in high-density planting.